DEVELOPING THE DESIGN OF CHARACTER EDUCATION THROUGH INTEGRATED CURRICULUM IN STATE ISLAMIC UNIVERSITY OF NORTH SUMATRA MEDAN - Mardianto Mardianto; Irwan S; Fauziah Nasution (UIN Sumatera Utara Medan, 2019)
This study aims to develop the design of character education through an integrated curriculum in learning activities at UIN of North Sumatra Medan. This research activity is expected to provide a direct contribution to learning activities at UIN of North Sumatra Medan. Specifically, the contribution of this research is expected to contribute to: (1) the lecturers in developing learning that is able to develop and educate student characters, (2) the students of UIN of North Sumatra Medan to have the character as expected by UIN of North Sumatra Medan curriculum, and (3) UIN of North Sumatra Medan in developing character-based learning program design. When character education is taught with an integrated approach in the curriculum, it is a strategic concept to strengthen the values of goodness for the students. This certainly requires a design that can be developed in learning activities for the classroom and implemented by lecturers to students.